2014
DOI: 10.1007/s10439-014-1197-z
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Hybrid III Head Impact Kinematics Using an Accelerometer and Gyroscope System in Ice Hockey Helmets

Abstract: Helmet-based instrumentation is used to study the biomechanics of concussion. The most extensively used systems estimate rotational acceleration from linear acceleration, but new instrumentation measures rotational velocity using gyroscopes, potentially reducing error. This study compared kinematics from an accelerometer and gyroscope-containing system to reference measures. A Hybrid III (HIII) adult male anthropometric test device head and neck was fit with two helmet brands, each instrumented with gForce Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 21 publications
0
33
0
1
Order By: Relevance
“…A strong correlation ( R 2 = 0.94) was also found between raw peak rotational velocity measured by the GFT and the Hybrid III ATD headform data. Campbell et al [104] supported the conclusions of Allison et al [101] regarding helmet brand-specific correction algorithms.…”
Section: Instrumented Helmets and Headgearmentioning
confidence: 74%
See 2 more Smart Citations
“…A strong correlation ( R 2 = 0.94) was also found between raw peak rotational velocity measured by the GFT and the Hybrid III ATD headform data. Campbell et al [104] supported the conclusions of Allison et al [101] regarding helmet brand-specific correction algorithms.…”
Section: Instrumented Helmets and Headgearmentioning
confidence: 74%
“…Allison et al [101] evaluated the accuracy of the GFT using a linear impactor, at speeds ranging from 1.5 to 5.0 m/s, to impact a hockey helmet mounted on a Hybrid III ATD head-neck system at various sites: facemask, side, rear-oblique, and rear. Relative to the peak linear acceleration data from the Hybrid III ATD headform, the raw data from the GFT demonstrated large differences of up to 150%, which was attributed to the lack of algorithm to transform the data to the centre of gravity of the head.…”
Section: Instrumented Helmets and Headgearmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors acknowledge the potential for spurious head impact measurement based on accelerometry of the helmet, and not the head (e.g., pounding helmet on ground while not on head) despite the effort in standardizing head impact measurement between study groups. While prior studies have indicated that GForce Tracker affixed in helmets can provide suitable impact‐monitoring, the authors acknowledge the potential for up to 10–40% error as has been suggested in the literature in accelerometry measures with GForce Tracker [Allison et al, ; Campbell et al, ]. Further efforts to achieve technology development and algorithmic solutions to accelerometry measurement error, for example, combining and synchronizing video information with wearable sensor recording to cross‐verify head impact events [Cortes et al, ], are needed in future studies.…”
Section: Discussionmentioning
confidence: 97%
“…Because of these findings, new helmet-based instrumentation systems, such as the gForce Tracker (Markham, ON), have been developed that use gyroscopes in combination with accelerometers to more accurately measure rotational kinematics. Preliminary studies show decreased errors when measured with ATD modeling [30].…”
Section: Hockeymentioning
confidence: 94%